Soil Stabilization on Cibingbin Village Roads Using Rice Husk Ash and Cement - Rama Indera Kusuma; Woelandari Fathonah; Enden Mina; Yuda Inayatullah (Jurnal Fondasi, 2023)
Soil is the foundation of civil buildings, and its function is to support and withstand structural loads. Many materials can be used as soil stabilization materials. For this soil stabilization, RHA and type 1 cement as stabilization materials were chosen. Soil samples were collected on Cibingbin Village Road, Cibaliung. The soil was mixed with RHA at 0%, 5%, 10%, 15%, and 20% with 20% cement as an additive with 0, 7, 14, and 28 days of curing time. Soil from Cibingbin village can be classified as high plasticity inorganic clay (CH) based on the USCS classification table. UCT result shows the most optimum RHA content is in the 5% variation. The highest unconfined compressive strength value is at 28 days of curing time with 5% RHA content and 20% cement with unconfined compressive value of 20.9 kg/cm2. According to the provisions of Bina Marga PUPR in 2018, the plasticity index value of the Cibingbin soil is 12.94%, which meets the requirements for making road subgrades plasticity index value below 15%.